Genetic and molecular mapping of chromosome region 85A in Drosophila melanogaster. - Jones, W.K.; Rawls, J.M. (Genetics, 1988)
Chromosome region 85A contains at least 12 genetic complementation groups, including the genes dhod, pink and hunchback. In order to better understand the organization of this chromosomal segment and to permit molecular studies of these genes, we have carried out a genetic analysis coupled with a chromosome walk to isolate the DNA containing these genes. Complementation tests with chromosomal deficiencies permitted unambiguous ordering of most of the complementation groups identified within the 85A region. Recombinant bacteriophage clones were isolated that collectively span over 120 kb of 85A DNA and these were used to produce a molecular map of the region. The breakpoint sites of a number of 85A chromosome rearrangements were localized on the molecular map, thereby delimiting regions of the DNA that contain the various genetic complementation groups.